Africa Agriculture Transformation Scorecard: performance and lessons. Southern African Development Community (SADC) - Matchaya, Greenwell C.; Nhlengethwa, Sibusiso; Panduleni, E.; Greffiths, Ikhothatseng Jacob; Fakudze, Bhekiwe (Regional Strategic Analysis and Knowledge Support System for Southern Africa, 2021)
This brief highlights the SADC region’s performance in the second BR and analyzes challenges faced and lessons learned by the region. The brief also reviews policy and programmatic changes in the SADC region induced by lessons from the inaugural 2017 and concludes by highlighting required policy actions for SADC to meet Malabo commitments by 2025.